High-performance concrete and preparation method thereof

By using modified bentonite and nanopotassium feldspar powder in concrete, the problem of insufficient mechanical properties and wear resistance of traditional concrete is solved, and the concrete performance with high compression, flexural and wear resistance is achieved.

CN119874300AActive Publication Date: 2025-04-25ZHEJIANG BUILDING MATLS GP CONSTR INDUSTRIALIZATION CO LTD

Patent Information

Application Number
CN202510372351.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

Traditional concrete has shortcomings in terms of mechanical properties and wear resistance, especially in terms of compressive strength, flexural strength and wear resistance.

Method used

Modified bentonite and nanopotassium feldspar powder are used as new additives. By adding octadecyl bishydroxyethyl methyl ammonium chloride and manganese and iron ions during the preparation process of modified bentonite to form stable iron-manganese oxides, enhancing the stability and wear resistance of bentonite, and combining with nanopotassium feldspar powder to improve the bonding strength between cement and aggregate.

Benefits of technology

The compressive strength, flexural strength and split strength of concrete are significantly improved, while the wear amount is reduced, and the overall mechanical properties and wear resistance of concrete are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete, and particularly relates to high-performance concrete and a preparation method thereof. The concrete is prepared from the following raw materials in parts by weight: 200 to 230 parts of cement, 10 to 20 parts of modified bentonite, 10 to 20 parts of nano potassium feldspar powder, 650 to 700 parts of fine aggregate, 950 to 1000 parts of coarse aggregate, 30 to 40 parts of mineral powder, 30 to 40 parts of fly ash, 5 to 10 parts of water reducing agent and 140 to 150 parts of water. The concrete provided by the invention has more excellent mechanical properties and wear resistance. Specifically, after the concrete is cured for 28 days, the compressive strength of the concrete is higher than 85.7 MPa, the breaking strength is higher than 9.5 MPa, the splitting strength is higher than 8.6 MPa, and the abrasion loss is lower than 0.24 kg / m < 2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to high-performance concrete and a preparation method thereof. Background Art

[0002] At present, one of the most widely used building materials in my country is concrete. Concrete is a general term for engineering composite materials in which aggregates are bonded into a whole by cementitious materials. Traditional concrete mainly includes cement, sand, aggregates, water and other components. The microstructure of concrete made with the above components is relatively rough, its mechanical properties are subject to certain limitations, and it usually performs poorly in terms of wear resistance. With the diversification of concrete application scenarios, higher requirements are placed on the mechanical properties and wear resistance of concrete.

[0003] Bentonite is a natural volcanic ash material and a common high-expansion clay, with montmorillonite as its main component. Bentonite is widely used in the field of building materials technology due to its cation exchange, expansion and plasticity. However, studies have shown that although adding bentonite to concrete can reduce the initial cracks inside the concrete and improve the crack resistance and deformation ability of the concrete, it will reduce the compressive strength and flexural strength of the concrete.

[0004] Potassium feldspar powder is a powder made of potassium-rich silicate minerals. It has the advantages of low melting point, long melting interval, high melting viscosity, and low fluidity, and is therefore used in the preparation of concrete. However, studies have found that potassium feldspar powder is relatively fragile, which in turn affects the mechanical properties and wear resistance of concrete.

[0005] Based on the above background, the present invention conducts a deeper study on the mechanical properties and wear resistance of concrete to accelerate the application of bentonite and potassium feldspar powder in concrete. Summary of the invention

[0006] In order to overcome the deficiencies of the prior art, one of the objects of the present invention is to provide a high performance concrete having excellent wear resistance and high mechanical properties.

[0007] The second object of the present invention is to provide a method for preparing high performance concrete with a simple preparation process.

[0008] One of the purposes of the present invention is achieved by the following technical solution: A high-performance concrete comprises the following raw materials in parts by weight: 200-230 parts of cement, 10-20 parts of modified bentonite, 10-20 parts of nano potassium feldspar powder, 650-700 parts of fine aggregate, 950-1000 parts of coarse aggregate, 30-40 parts of mineral powder, 30-40 parts of fly ash, 5-10 parts of water reducer, and 140-150 parts of water; The preparation process of the modified bentonite is as follows: (1) taking bentonite and adding it to an aqueous solution of octadecyl bis(hydroxyethyl)methylammonium chloride for heating treatment to obtain pretreated bentonite; (2) adding the bentonite, manganese nitrate and ferric nitrate pretreated in step (1) to water to obtain a mixed solution A; adding sodium carbonate and sodium phosphate to water to obtain a mixed solution B; (3) The mixed solution A of step (2) is heated to 80-90° C., and then the mixed solution B of step (2) is added under stirring to carry out heating reaction. After the reaction is completed, the product is collected and purified, and the product is calcined to obtain modified bentonite.

[0009] Preferably, the fine aggregate is natural river sand with a particle size of 1-2 mm; the coarse aggregate is primary crushed stone with a particle size of 5-20 mm; the mineral powder is S95 grade slag powder; and the fly ash powder is grade I fly ash.

[0010] Preferably, in step (1), the ratio of bentonite to the aqueous solution of octadecyl bis(hydroxyethyl)methylammonium chloride is 1 g: (10-15) mL; and the concentration of the aqueous solution of octadecyl bis(hydroxyethyl)methylammonium chloride is 25-32 g / L.

[0011] Preferably, the temperature of the heating treatment in step (1) is 50-60° C., and the heating treatment time is 2.5-4 h.

[0012] Preferably, the mass ratio of the pretreated bentonite, manganese nitrate, iron nitrate and water in step (2) is 1: (0.5-1.5): (1-2): (15-20).

[0013] Preferably, the mass ratio of sodium carbonate, sodium phosphate and water in step (2) is 1:(0.2-0.4):(5-7).

[0014] Preferably, in step (3), the mass ratio of the pretreated bentonite in the mixed solution A to the sodium carbonate in the mixed solution B is 1:(1-1.5); Preferably, the temperature of the heating reaction in step (3) is 80-90° C., and the heating reaction time is 4-6 h.

[0015] Preferably, the calcination temperature in step (3) is 200-300° C., and the calcination time is 5-7 h.

[0016] Preferably, the water reducer is a polycarboxylate water reducer.

[0017] More preferably, the polycarboxylate water reducer is PCE-102 polycarboxylate water reducer.

[0018] The second object of the present invention is achieved by adopting the following technical solution: The method for preparing the high performance concrete comprises the following steps: According to the weight ratio, fine aggregate and coarse aggregate are mixed evenly, and then water, fly ash powder, cement, mineral powder, water reducing agent, modified bentonite and nano potassium feldspar powder are added and mixed evenly.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The modified bentonite of the present invention has high stability and wear resistance. Specifically, octadecyl bis(hydroxyethyl)methyl ammonium chloride is added to the bentonite to weaken the bonding force between bentonite layers; then further reaction allows manganese and iron ions to enter the bentonite layers, and after calcination, stable iron-manganese oxides are formed, thereby enhancing the stability and wear resistance of the bentonite. In addition, the modified bentonite also has good film-forming properties, and its use in combination with nano-potash feldspar can improve the bonding strength between cement and aggregate, thereby increasing the locking force between aggregates, and achieving the purpose of improving the mechanical properties of concrete.

[0020] The concrete of the present invention has more excellent mechanical properties and wear resistance. Specifically, after curing for 28 days, the compressive strength of the concrete is higher than 85.7MPa, the flexural strength is higher than 9.5MPa, the splitting strength is higher than 8.6MPa, and the wear loss is lower than 0.24kg / m2. DETAILED DESCRIPTION

[0021] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or replacements can also be made, all of which should be deemed to belong to the protection scope of the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0022] The cement involved in the present invention is 42.5 ordinary Portland cement; the fine aggregate is natural river sand with a particle size of 1-2 mm; the coarse aggregate is first-grade crushed stone with a particle size of 5-20 mm; the mineral powder is S95-grade slag powder with a density of 2.9 g / cm3, a specific surface area of ​​450 m2 / kg, a water content of 0.2%, and a 28d activity index of 95%; the fly ash powder is Class I fly ash; and the polycarboxylate water reducer is PCE-102 polycarboxylate water reducer.

[0023] 1. Preparation Example Preparation Example 1 Preparation Example 1 provides a modified bentonite, and the specific preparation process is as follows: (1) Bentonite was added to a 30 g / L aqueous solution of octadecyl bis(hydroxyethyl)methylammonium chloride in a ratio of 1 g:12 mL, and the mixture was heated at 54° C. for 3 h to obtain pretreated bentonite.

[0024] (2) adding the bentonite, manganese nitrate and ferric nitrate pretreated in step (1) to water in a mass ratio of 1:1:1.5:18 to obtain a mixed solution A; Sodium carbonate and sodium phosphate were added to water according to the mass ratio of sodium carbonate, sodium phosphate and water of 1:0.3:6 to obtain a mixed solution B.

[0025] (3) The mixed solution A of step (2) is heated to 85° C., and then the mixed solution B of step (2) is added under stirring, wherein the mass ratio of the pretreated bentonite in the mixed solution A to the sodium carbonate in the mixed solution B is 1:1. The mixture is heated at 85° C. for 5 h. After the reaction is completed, the product is filtered, washed, and dried to collect the product, and the product is calcined at 220° C. for 5.7 h to obtain modified bentonite.

[0026] Preparation Example 2 Preparation Example 2 provides a modified bentonite, and the specific preparation process is as follows: (1) Bentonite was added to an aqueous solution of 32 g / L octadecyl bis(hydroxyethyl)methylammonium chloride in a ratio of 1 g:15 mL, and the mixture was heated at 60° C. for 2.5 h to obtain pretreated bentonite.

[0027] (2) adding the bentonite, manganese nitrate and ferric nitrate pretreated in step (1) to water in a mass ratio of 1:1.5:2:20 to obtain a mixed solution A; Sodium carbonate and sodium phosphate were added to water according to the mass ratio of sodium carbonate, sodium phosphate and water of 1:0.4:7 to obtain a mixed solution B.

[0028] (3) The mixed solution A of step (2) is heated to 90° C., and then the mixed solution B of step (2) is added under stirring, wherein the mass ratio of the pretreated bentonite in the mixed solution A to the sodium carbonate in the mixed solution B is 1:1.2. The mixture is heated at 90° C. for 4 h. After the reaction is completed, the mixture is filtered, washed, dried, and the product is collected. The product is calcined at 300° C. for 5 h to obtain modified bentonite.

[0029] Preparation Example 3 Preparation Example 3 provides a modified bentonite, and the specific preparation process is as follows: (1) Bentonite was added to an aqueous solution of 25 g / L octadecyl bis(hydroxyethyl)methylammonium chloride in a ratio of 1 g:10 mL, and the mixture was heated at 50° C. for 4 h to obtain pretreated bentonite.

[0030] (2) adding the bentonite, manganese nitrate and ferric nitrate pretreated in step (1) to water in a mass ratio of 1:0.5:1:15 to obtain a mixed solution A; Sodium carbonate and sodium phosphate were added to water according to the mass ratio of sodium carbonate, sodium phosphate and water of 1:0.2:5 to obtain a mixed solution B.

[0031] (3) The mixed solution A of step (2) is heated to 80° C., and then the mixed solution B of step (2) is added under stirring, wherein the mass ratio of the pretreated bentonite in the mixed solution A to the sodium carbonate in the mixed solution B is 1:1.5. The mixture is heated at 80° C. for 6 h. After the reaction is completed, the mixture is filtered, washed, dried, and the product is collected. The product is calcined at 200° C. for 7 h to obtain modified bentonite.

[0032] 2. Example

[0033] Example 1

[0034] Example 1 provides a high-performance concrete, which is composed of the following raw materials in parts by weight: 210 parts of cement, 12 parts of modified bentonite obtained in Preparation Example 1, 15 parts of nano potassium feldspar powder, 680 parts of fine aggregate, 970 parts of coarse aggregate, 33 parts of mineral powder, 36 parts of fly ash, 7 parts of polycarboxylic acid water reducer, and 142 parts of water.

[0035] Example 1 also provides a method for preparing the high performance concrete, which is as follows: According to the above weight ratio, fine aggregate and coarse aggregate are mixed evenly, and then water, fly ash powder, cement, mineral powder, polycarboxylic acid water reducer, modified bentonite and nano potassium feldspar powder are added and mixed evenly.

[0036] Example 2

[0037] Example 2 provides a high-performance concrete, which is composed of the following raw materials in parts by weight: 230 parts of cement, 20 parts of modified bentonite obtained in Preparation Example 2, 20 parts of nano-potash feldspar powder, 700 parts of fine aggregate, 1000 parts of coarse aggregate, 40 parts of mineral powder, 40 parts of fly ash, 10 parts of polycarboxylic acid water reducer, and 150 parts of water.

[0038] Example 2 also provides a method for preparing the high performance concrete, which is as follows: According to the above weight ratio, fine aggregate and coarse aggregate are mixed evenly, and then water, fly ash powder, cement, mineral powder, polycarboxylic acid water reducer, modified bentonite and nano potassium feldspar powder are added and mixed evenly.

[0039] Example 3

[0040] Example 3 provides a high-performance concrete, which is composed of the following raw materials in parts by weight: 200 parts of cement, 10 parts of modified bentonite obtained in Preparation Example 3, 10 parts of nano potassium feldspar powder, 650 parts of fine aggregate, 950 parts of coarse aggregate, 30 parts of mineral powder, 30 parts of fly ash, 5 parts of polycarboxylic acid water reducer, and 140 parts of water.

[0041] Example 3 also provides a method for preparing the high performance concrete, which is as follows: According to the above weight ratio, fine aggregate and coarse aggregate are mixed evenly, and then water, fly ash powder, cement, mineral powder, polycarboxylic acid water reducer, modified bentonite and nano potassium feldspar powder are added and mixed evenly.

[0042] 3. Comparative ratio Comparative Example 1 Comparative Example 1 provides a concrete, which is composed of the following raw materials in parts by weight: 210 parts of cement, 12 parts of bentonite, 15 parts of nano potassium feldspar powder, 680 parts of fine aggregate, 970 parts of coarse aggregate, 33 parts of mineral powder, 36 parts of fly ash, 7 parts of polycarboxylic acid water reducer, and 142 parts of water, and the rest is consistent with Example 1.

[0043] Comparative Example 2 Comparative Example 2 provides a concrete, which is composed of the following raw materials in parts by weight: 210 parts of cement, 12 parts of modified bentonite obtained in Preparation Example 1, 15 parts of potassium feldspar powder, 680 parts of fine aggregate, 970 parts of coarse aggregate, 33 parts of mineral powder, 36 parts of fly ash, 7 parts of polycarboxylic acid water reducer, and 142 parts of water, and the rest is consistent with Example 1.

[0044] Comparative Example 3 Comparative Example 3 provides a concrete, which is composed of the following raw materials in parts by weight: 210 parts of cement, 27 parts of modified bentonite obtained in Preparation Example 1, 680 parts of fine aggregate, 970 parts of coarse aggregate, 33 parts of mineral powder, 36 parts of fly ash, 7 parts of polycarboxylic acid water reducer, and 142 parts of water, and the rest is consistent with Example 1.

[0045] Comparative Example 4 Comparative Example 4 provides a concrete, which is composed of the following raw materials in parts by weight: 210 parts of cement, 27 parts of nano potassium feldspar powder, 680 parts of fine aggregate, 970 parts of coarse aggregate, 33 parts of mineral powder, 36 parts of fly ash, 7 parts of polycarboxylic acid water reducer, and 142 parts of water, and the rest is consistent with Example 1.

[0046] 4. Test examples The concrete prepared in Examples 1-3 and Comparative Examples 1-4 was subjected to performance tests after curing for 28 days under standard conditions, as follows: Compressive strength, flexural strength, splitting strength: tested according to GB / T50081-2019 method, the experimental results are shown in Table 1; Wear resistance: The test was carried out according to JTGE30-2005 method. The experimental results are shown in Table 1.

[0047]

[0048] It can be seen from Table 1 that the concrete prepared in Examples 1-3 has greater compressive strength, flexural strength, splitting strength, and less wear. The above results show that the concrete prepared in Examples 1-3 has more excellent mechanical properties and wear resistance.

[0049] It can be seen from the data in Table 1 that in Comparative Example 1, modified bentonite is replaced by bentonite; in Comparative Example 2, nano potassium feldspar powder is replaced by potassium feldspar powder; in Comparative Example 3, nano potassium feldspar is omitted and the amount of modified bentonite is increased; in Comparative Example 4, modified bentonite is omitted and the amount of nano potassium feldspar is increased, and the mechanical properties of the prepared concrete are significantly reduced. The above results show that the combination of nano potassium feldspar and modified bentonite can effectively improve the mechanical properties of concrete. This is because modified bentonite has good film-forming properties, and its combination with nano potassium feldspar can improve the bonding strength between cement and aggregate, thereby increasing the locking force between aggregates and achieving the purpose of improving the mechanical properties of concrete.

[0050] Furthermore, the wear resistance of the concrete obtained in Comparative Examples 1 and 4 is significantly reduced. The above results show that the modified bentonite of the present invention can affect the wear resistance of concrete. The present invention adds octadecyl bis(hydroxyethyl)methylammonium chloride to bentonite to weaken the binding force between bentonite layers; then further reacts to allow manganese and iron ions to enter the bentonite layers, and after calcination, stable iron-manganese oxides are formed, thereby enhancing the stability and wear resistance of the bentonite.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.

Claims

1. A high performance concrete, characterized in that: The raw materials include the following parts by weight: 200-230 parts of cement, 10-20 parts of modified bentonite, 10-20 parts of nano potassium feldspar powder, 650-700 parts of fine aggregate, 950-1000 parts of coarse aggregate, 30-40 parts of mineral powder, 30-40 parts of fly ash, 5-10 parts of water reducer, and 140-150 parts of water; The preparation process of the modified bentonite is as follows: (1) taking bentonite and adding it to an aqueous solution of octadecyl bis(hydroxyethyl)methylammonium chloride for heating treatment to obtain pretreated bentonite; (2) adding the bentonite, manganese nitrate and ferric nitrate pretreated in step (1) to water to obtain a mixed solution A; adding sodium carbonate and sodium phosphate to water to obtain a mixed solution B; (3) The mixed solution A of step (2) is heated to 80-90° C., and then the mixed solution B of step (2) is added under stirring to carry out heating reaction. After the reaction is completed, the product is collected and purified, and the product is calcined to obtain modified bentonite.

2. The high performance concrete according to claim 1, characterized in that: In step (1), the ratio of bentonite to the aqueous solution of octadecyl bis(hydroxyethyl)methylammonium chloride is 1 g: (10-15) mL; the concentration of the aqueous solution of octadecyl bis(hydroxyethyl)methylammonium chloride is 25-32 g / L.

3. The high performance concrete according to claim 1, characterized in that: The temperature of the heating treatment in step (1) is 50-60°C, and the heating treatment time is 2.5-4h.

4. The high performance concrete according to claim 1, characterized in that: The mass ratio of the pretreated bentonite, manganese nitrate, iron nitrate and water in step (2) is 1: (0.5-1.5): (1-2): (15-20).

5. The high performance concrete according to claim 1, characterized in that: The mass ratio of sodium carbonate, sodium phosphate and water in step (2) is 1:(0.2-0.4):(5-7).

6. The high performance concrete according to claim 1, characterized in that: In step (3), the mass ratio of the pretreated bentonite in the mixed solution A to the sodium carbonate in the mixed solution B is 1:(1-1.5).

7. The high performance concrete according to claim 1, characterized in that: The temperature of the heating reaction in step (3) is 80-90° C., and the heating reaction time is 4-6 hours.

8. The high performance concrete according to claim 1, characterized in that: The calcination temperature in step (3) is 200-300°C, and the calcination time is 5-7h.

9. The high performance concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.

10. The method for preparing high performance concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: According to the weight ratio, fine aggregate and coarse aggregate are mixed evenly, and then water, fly ash powder, cement, mineral powder, water reducing agent, modified bentonite and nano potassium feldspar powder are added and mixed evenly.

Citation Information

Patent Citations

  • High-performance concrete applying machine-made sand and preparation method of high-performance concrete

    CN113480267A

  • Environment-friendly high-performance concrete and preparation process thereof

    CN117550853A

  • Ceramic tile and preparation method thereof

    CN119409482A

  • Method for activation of bentonites

    US3909454A

Cited By

  • High-performance concrete and preparation method thereof

    CN121405407A

  • A high performance concrete and a method for preparing the same

    CN121405407B